2019
DOI: 10.1021/acsanm.9b01044
|View full text |Cite
|
Sign up to set email alerts
|

Regulating the Sensitivity and Operating Temperatures by Morphology Engineering of 2D ZnO Nanostructures and 3D ZnO Microstructures for the Detection of Organic-Amines

Abstract: Two-dimensional (2D) materials possess unique properties and advantages in catalysis, photo/-electronic and sensor devices. Here, we proposed a facile route to synthesize 2D ZnO nanoplates with grids by the oxalic-acid-assisted hydrothermal method. Morphology evolutions of ZnO from 3D flower-like microparticles to 2D nanonets were achieved by changing the heat-treatment temperature. By substitution for oxalic acid, 3D ZnO cagelike spheres and hexagonal prism were obtained. The results show that 2D and 3D morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…The rapid progress of materials research has enabled significant advancement of gas sensor technology. [ 7–9 ] Currently, metal oxide semiconductors (MOS) are widely used in gas sensors for VOC detection, [ 10,11 ] especially SnO 2 , [ 12,13 ] ZnO, [ 14,15 ] WO x , [ 16–18 ] and Co 3 O 4 [ 19,20 ] have been extensively studied as TEA sensors. However, the high operating temperature and poor selectivity of MOS remarkably limits its practical applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid progress of materials research has enabled significant advancement of gas sensor technology. [ 7–9 ] Currently, metal oxide semiconductors (MOS) are widely used in gas sensors for VOC detection, [ 10,11 ] especially SnO 2 , [ 12,13 ] ZnO, [ 14,15 ] WO x , [ 16–18 ] and Co 3 O 4 [ 19,20 ] have been extensively studied as TEA sensors. However, the high operating temperature and poor selectivity of MOS remarkably limits its practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8,21 ] Substantial efforts have been made by researchers to address these obstacles. Generally these strategies include the design of specific nanostructures, [ 14,22 ] fabrication of heterostructures, [ 23–25 ] surface modification of MOS by catalysts, [ 26 ] and creation of atomic defects such as oxygen vacancy. [ 15,27 ] These approaches have been widely used to change or improve the electronic and chemical properties at the materials’ surface or interface, [ 14,28 ] and have led to a substantial amount of reports of improved TEA sensors.…”
Section: Introductionmentioning
confidence: 99%
“…However, most bulk transition metal oxides have strong interlayer ionic bonds and no obvious layered structure, which makes it difficult to obtain their 2D nanosheets by exfoliation. Non-vdW oxides that are commonly used include In 2 O 3 , 63 TiO 2 , [64][65][66][67][68][69][70][71][72][73] CeO 2 , 74 Gd 2 O 3 , 75 NiO, [76][77][78][79] [87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105] ZnO, [106][107][108][109][110][111][112][113][114] WO 3 , [48][49][50] and so on. Due to the 3D block structure, only the outermost atoms and active sites on the surface can play a role, while other atoms and active sites are covered, which is far from the full utiliza...…”
Section: Typical 2d Non-van Der Waals Oxidesmentioning
confidence: 99%
“…This technology can be used to prepare optically passivated mixed metal oxide films as counter electrodes with high light transmittance and good cycling stability. Dahal et al 138 demonstrated the insertion of a grown 2D FeO layer between CVDgrown graphene and a Pt (111) substrate by continuously inserting iron and oxygen, which could separate the graphene from the metal substrate. They showed that metal-stabilized 2D oxidized monolayers can grow between graphene and metal substrates to form 2D heterostructures that can adjust films, grown at an oxygen content of 1/16 and 1/32 and annealed at 500 °C/1 h. The substrates used are ordinary glasses.…”
Section: Chemical Vapor Deposition (Cvd)mentioning
confidence: 99%
“…BP has also been used as an efficient artificial substrate for DNA replication . Layered transition-metal oxides have been less explored; one of the reasons could be their wide band gap, which renders them electrically insulating. However, a new study has shown that n-type conduction can be induced in α-MoO 3 either by H + -ion intercalation, which creates oxygen vacancies, or by fluorine doping . Oxygen vacancies can also play an important role in enhancing the gas-sensing capabilities in devices based on α-MoO 3 .…”
Section: Inorganic 2d Materialsmentioning
confidence: 99%